Deutsche Siedlungen in Südaustralien: Entstehung und kulturlandschaftliche Entwicklung eines Kolonisationsraumes - Erdmann, Claudia (ERDKUNDE, 1984)
South Australia’s colonization was strongly connected with German Lutherans, who in 1838 first decided to leave their agricultural communities in Silesia. However, though officially religious reasons caused these families to emigrate under the guidance of their pastor, their poor financial situation must have been the other important motive for starting a new life in the young colony. Well, away from the capital, and in accordance with tradition, they cleared the woods and independently created their own cultural landscape in the Barossa Valley. Forest villages (Waldhufendorfer) with half-timbered, originally straw-thatched houses, small units and mixed farming were the main characteristics. Many of these can still be found in the valley, as in fact the influence of this group never ceased. Chain migration initiated by letter contacts with friends and relatives in the home country helped to preserve the consciousness of their origins just as much as did the continuous influence that Lutheran pastors exercised in their communities - their own jurisdiction at the beginning, marriages between Lutherans only, and education in German until the 1870s. Thus not only is South Australia the first state on the continent where Germans took an essential part in colonization but is at the same time the centre from whence descendants of this minority group were to leave for the pioneer fringe in other parts of Australia.